A four-layer coated iron-based nanocrystalline soft magnetic powder core and preparation method thereof

Through the four-layer coating process, the problems of impurities introduction and unstable coating layer in the preparation process of amorphous nanocrystalline soft magnetic powder core are solved, and the iron-based nanocrystalline soft magnetic powder core with low magnetic loss and high magnetic permeability are realized. Suitable for high frequency and high temperature applications.

CN115083721BActive Publication Date: 2024-12-17GUANGDONG INST OF NEW MATERIALS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210755578.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-29
Publication Date
2024-12-17
Estimated Expiration
2042-06-29

AI Technical Summary

Technical Problem

The existing amorphous nanocrystalline soft magnetic powder cores are prone to introduce impurities during the preparation process, resulting in uneven powder components, high magnetic loss, low saturation magnetic induction strength, and unstable insulation coating, which is difficult to meet the requirements of high frequency and high temperature.

Method used

Four-layer coating process is adopted, namely passivation layer, SiO2 layer, stearate layer and silicone resin layer. The thickness of the coating layer is <40nm. The magnetic powder is protected by the passivation layer, the SiO2 layer increases the resistivity, and stearic acid is stearic acid. The salt layer increases compaction density and oxide formation, and the silicone resin layer increases bonding and SiO2 formation, reducing eddy current magnetic loss.

Benefits of technology

It has achieved a low magnetic loss and high magnetic permeability iron-based nanocrystal soft magnetic powder core, with improved cladding stability, increased resistivity, and reduced damage to magnetic properties by non-magnetic substances, making it suitable for high-frequency and high-temperature applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115083721B_ABST
    Figure CN115083721B_ABST
Patent Text Reader

Abstract

The present invention discloses a four-layer coated iron-based nanocrystalline soft magnetic powder core and a preparation method thereof, and belongs to the technical field of alloy soft magnetic powder core. The present invention coats four layers of coating on the surface of the iron-based nanocrystalline, not only making the coating layer of the soft magnetic powder core more stable, obtaining a higher resistivity to reduce the eddy current magnetic loss of the soft magnetic powder core, but also the thickness of the coating layer is less than 40nm, which greatly reduces the damage of the non-magnetic material to the magnetic properties of the soft magnetic powder core; at the same time, the coated nanocrystalline magnetic powder is subjected to a heat treatment process without heat preservation and rapid cooling, so as to achieve high magnetic permeability and low magnetic loss of the four-layer coated iron-based nanocrystalline soft magnetic powder core; under the test conditions of Bm=0.1T and 50kHz, the magnetic permeability of the four-layer coated iron-based nanocrystalline soft magnetic powder core of the present invention is greater than 80, and the magnetic loss is less than 150kW / m 3 , which has the advantages of low magnetic loss and high magnetic permeability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of alloy soft magnetic powder cores, and in particular to a four-layer coated iron-based nanocrystalline soft magnetic powder core and a preparation method thereof. Background Art

[0002] Magnetic powder core is a soft magnetic material made by mixing and pressing magnetic powder and insulating medium. The insulating medium can isolate the powder particles, reduce eddy current magnetic loss and magnetic permeability, so as to ensure that the magnetic powder core has constant magnetic permeability at high frequency; magnetic powder core has excellent comprehensive magnetic properties, such as high saturation magnetization intensity, good frequency stability of constant effective magnetic permeability, high resistivity, and low core magnetic loss; soft magnetic powder core material can be designed into electronic components of various shapes such as "E" shape, "POT" shape, ring shape and strip shape. The plasticity of shape makes it play an important role in the electronic components market. At present, there are various types of soft magnetic powder cores on the market, such as iron, iron silicon aluminum, iron nickel, and new amorphous and nanocrystalline alloys. Compared with other magnetic powder cores, amorphous nanocrystalline magnetic powder cores have higher magnetic permeability, lower iron loss, and better high-frequency characteristics; its preparation process firstly makes amorphous strips by melt rapid quenching, and then mechanically crushes them into amorphous nanocrystalline magnetic powder; then the amorphous nanocrystalline magnetic powder particles are passivated and inorganic / organic insulation coated; the coated amorphous nanocrystalline magnetic powder is then placed in a mold for pressing and forming; finally, the formed magnetic powder core is subjected to a suitable annealing process under vacuum or inert gas to obtain a high-performance amorphous nanocrystalline magnetic powder core.

[0003] Since amorphous nanocrystalline magnetic powder is prepared by strip crushing, impurities are easily introduced during the ball milling process, resulting in uneven powder composition, and the obtained powder is mostly in the form of flakes with sharp edges and irregular shapes, which are difficult to coat, affecting the insulation effect of the magnetic powder surface, resulting in high magnetic loss of the magnetic powder core. At the same time, its saturation magnetic induction intensity is low, resulting in poor DC bias resistance of the magnetic powder core. In addition, a coating agent with a relatively single composition will cause the insulation coating of the magnetic powder core to be unstable. For example, the magnetic powder core coated with an organic insulating layer has low thermal stability and cannot be annealed at high temperature. The mechanical properties and related magnetic properties of the obtained magnetic powder core cannot meet the application requirements well. The brittleness of the inorganic coating layer limits the high-density magnetic powder core obtained in the pressing process. The organic-inorganic composite coating method retains the advantages of both organic and inorganic, so more and more research is being conducted. However, due to the poor regulation of factors such as the uniformity and thickness of the four-layer coating, the magnetic properties of the magnetic powder core are affected.

[0004] As basic electronic components develop towards miniaturization, higher frequency and higher efficiency, amorphous and nanocrystalline magnetic powders need to have lower core magnetic loss and higher effective magnetic permeability; therefore, the development of an amorphous nanocrystalline magnetic powder core with excellent performance and its preparation method has become one of the current research hotspots in amorphous nanocrystalline soft magnetic powder core materials. Summary of the invention

[0005] The object of the present invention is to overcome the above-mentioned deficiencies of the prior art and to provide a four-layer coated iron-based nanocrystalline soft magnetic powder core with low magnetic loss and high magnetic permeability and a preparation method thereof.

[0006] To achieve the above-mentioned purpose, the technical solution adopted by the present invention is: a four-layer coated iron-based nanocrystalline soft magnetic powder core, the four-layer coated iron-based nanocrystalline soft magnetic powder core is composed of iron-based nanocrystals and coating layers, the coating layers are respectively a passivation layer, a SiO2 layer, a stearate layer and a silicone resin layer from the inside to the outside, and the thickness of the coating layer is less than 40nm.

[0007] The present invention coats the surface of the iron-based nanocrystal with four coating layers. The passivation layer can form a passivation film on the surface of the iron-based nanocrystal magnetic powder, and the passivation film plays a role in protecting the iron-based nanocrystal magnetic powder in the subsequent coating process; the SiO2 layer has the characteristics of high thermal stability and high resistivity. It is attached to the surface of the passivated iron-based nanocrystal magnetic powder, which can avoid direct contact between the magnetic powders and also increase the resistivity between the magnetic powders, thereby achieving the purpose of reducing eddy current magnetic loss; the stearate layer can be used as a lubricant to increase the compaction density of the subsequent magnetic powder in the pressing process to form a highly densified magnetic powder core structure, and on the other hand, the stearate layer can be used as a lubricant to increase the compaction density of the subsequent magnetic powder in the pressing process to form a highly densified magnetic powder core structure. The acid salt can also be decomposed in the subsequent heat treatment process to form oxides on the surface of the magnetic powder, thereby increasing the core resistivity of the magnetic powder core, thereby achieving the purpose of reducing eddy current magnetic loss; the silicone resin layer can be used as a binder to make the magnetic powder core easier to be pressed and formed. On the other hand, the silicone resin can form SiO2 on the surface of the magnetic powder during the subsequent heat treatment process, thereby further increasing the core resistivity of the magnetic powder core, thereby achieving the purpose of reducing eddy current magnetic loss; the present invention coats the surface of the iron-based nanocrystal with four layers of coating, which not only makes the coating layer of the soft magnetic powder core more stable, but also has a higher resistivity to reduce the eddy current magnetic loss of the soft magnetic powder core.

[0008] The inventors further discovered that the thickness of the coating layer of the present invention is less than 40 nm, which greatly reduces the damage of the non-magnetic material to the magnetic properties of the soft magnetic powder core.

[0009] Another object of the present invention is to provide a method for preparing the four-layer coated iron-based nanocrystalline soft magnetic powder core, comprising the following steps:

[0010] S1. Pretreatment: crushing the iron-based nanocrystals into flaky powder to obtain nanocrystalline magnetic powder;

[0011] S2. One-layer coating: dissolving a strong acid or a medium-strong acid in ethanol or acetone to form a mixed solution, and adding the nanocrystalline magnetic powder to stir, and after the ethanol or acetone is completely volatilized, a passivation layer is formed on the surface of the nanocrystalline magnetic powder to obtain the passivated nanocrystalline magnetic powder;

[0012] S3, second layer coating: dissolve polyvinyl pyrrolidone (PVP) in anhydrous ethanol and stir until the solution is uniform and transparent, add the passivated nanocrystalline magnetic powder, continue stirring for 0.5-1h, pour out the supernatant, then drop NH3·H2O ethanol solution into it, continue stirring for 10-30min, then drop a mixed solution of tetraethyl silicate and anhydrous ethanol into the above mixed solution and stir for 1-2h, finally wash the passivated nanocrystalline magnetic powder with anhydrous ethanol and dry it at 80-100℃, thus completing the second layer coating of the nanocrystalline magnetic powder;

[0013] S4, three-layer coating: adding the magnetic powder obtained in step S3 to an ethanol or acetone solution of stearate, stirring until the ethanol or acetone is completely volatilized, so that the stearate is evenly coated on the surface of the magnetic powder obtained in step S3, that is, the third layer coating of the nanocrystalline magnetic powder is completed;

[0014] S5, four-layer coating: adding the magnetic powder obtained in step S4 to an ethanol or acetone solution of an organic silicone resin, and stirring until the ethanol or acetone is completely volatilized, thus completing the fourth layer coating of the nanocrystalline magnetic powder;

[0015] S6, pressing the magnetic powder obtained in step S5 to obtain an amorphous composite soft magnetic powder core, and then heat treating the amorphous composite magnetic powder core in a nitrogen atmosphere to obtain the four-layer coated iron-based amorphous nanocrystalline soft magnetic composite powder core.

[0016] Preferably, in step S1, the iron-based nanocrystals are Fe 73.5 Si 13.5 B9Cu1Nb3.

[0017] More preferably, in step S1, the iron-based nanocrystals are crushed to a median diameter D by ball milling. 50 70-80μm.

[0018] Preferably, in step S2, the strong acid or medium-strong acid is nitric acid or phosphoric acid.

[0019] Preferably, in step S2, the mass ratio of strong acid or medium-strong acid to nanocrystalline magnetic powder is 1:200-1000.

[0020] Preferably, in step S3, the stirring speed for dissolving PVP in ethanol is 20-80 rpm.

[0021] Preferably, in step S3, the concentration of the passivated nanocrystalline magnetic powder dissolved in anhydrous ethanol is 1 g / ml.

[0022] Preferably, in step S3, the mass ratio of the passivated nanocrystalline magnetic powder to PVP is 1:20-30.

[0023] Preferably, in step S3, in the ethanol solution of NH3·H2O, the mass ratio of deionized water to anhydrous ethanol is 1:1.

[0024] Preferably, in step S3, the mass ratio of the ethanol solution of NH3·H2O to the passivated nanocrystalline magnetic powder is 2:1.

[0025] It should be noted that in step S3, the volume of NH3·H2O needs to be determined according to the ethanol solution of NH3·H2O, that is, the pH of the ethanol solution of NH3·H2O is ensured to be 10-11.

[0026] Preferably, in step S3, the concentration of the passivated nanocrystalline magnetic powder dissolved in TEOS is 0.05-0.15 ml / g.

[0027] Preferably, in step S5, the stearate is zinc stearate.

[0028] Preferably, in step S4, the mass ratio of stearate to magnetic powder is 1:50-200.

[0029] Preferably, in step S5, the mass ratio of the silicone resin to the magnetic powder obtained in S4 is 1:50-200.

[0030] Preferably, in steps S2, S4 and S5, the stirring speed is ≤60 rpm.

[0031] It should be noted that in steps S2, S4 and S5 of the present invention, the volume of ethanol or acetone only needs to completely cover the nanocrystalline magnetic powder.

[0032] Preferably, in step S6, the pressure of the pressing molding is 1800-2400 MPa.

[0033] Preferably, in step S6, the heat treatment is specifically as follows: placing the amorphous composite soft magnetic powder core in a tubular furnace, exhausting the air in the furnace, then introducing nitrogen, first heating to 480-510°C, keeping warm for 15-60 minutes, and a heating rate of 1-20°C / min, and then heating to 540-560°C, and a heating rate of 1-5°C / min; when reaching 540-560°C, stop heating, open the furnace of the tubular furnace and increase the nitrogen flow rate to obtain the four-layer coated iron-based nanocrystalline soft magnetic powder core; increase the heat dissipation in the furnace by removing the furnace heating heat source, and at the same time take away a large amount of heat of the iron-based amorphous nanocrystalline soft magnetic composite powder core in the furnace cavity through nitrogen to ensure cooling to room temperature.

[0034] The purpose of the heat treatment process of the present invention is to precipitate a large number of α-Fe(Si) nanocrystals on the amorphous matrix to obtain the iron-based amorphous nanocrystalline soft magnetic composite powder core; and the content of the α-Fe(Si) nanocrystals is mainly determined by the heat treatment temperature, and the percentage of the amorphous matrix phase and the α-Fe(Si) nanocrystalline phase is the determining factor of the magnetic properties of the powder core. Therefore, it is necessary to strictly control the heat treatment temperature to induce the amorphous matrix to undergo a crystallization reaction, and to reduce the insulation time of the material to reduce the magnetic loss of the insulating coating layer in the high temperature environment, thereby effectively and significantly improving the magnetic permeability of the magnetic powder core and reducing its magnetic loss, and having better frequency stability.

[0035] The beneficial effects of the present invention are as follows: by coating four layers of coating on the surface of the iron-based nanocrystal, the coating of the soft magnetic powder core is not only more stable, but also a higher resistivity is obtained to reduce the eddy current magnetic loss of the soft magnetic powder core. Moreover, the thickness of the coating layer is less than 40nm, which greatly reduces the damage of the non-magnetic material to the magnetic properties of the soft magnetic powder core. At the same time, a heat treatment process without heat preservation and rapid cooling is adopted for the coated nanocrystalline magnetic powder, so that the high magnetic permeability and low magnetic loss of the four-layer coated iron-based nanocrystalline soft magnetic powder core are achieved. Under the test conditions of Bm=0.1T and 50kHz, the magnetic permeability of the four-layer coated iron-based nanocrystalline soft magnetic powder core is greater than 80, and the magnetic loss is less than 150kW / m 3 , showing the characteristics of low magnetic loss and high magnetic permeability. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is a microscopic morphology of the four-layer coated iron-based nanocrystalline soft magnetic powder core described in Example 1-2.

[0037] Figure 2 This is the magnetic permeability-frequency diagram of the four-layer coated iron-based nanocrystalline soft magnetic powder core described in Example 1-4 and Comparative Example 1-2.

[0038] Figure 3 This is a magnetic loss-frequency diagram of the four-layer coated iron-based nanocrystalline soft magnetic powder core described in Example 1-4 and Comparative Example 1-2. DETAILED DESCRIPTION

[0039] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.

[0040] Example 1

[0041] An embodiment of a four-layer coated iron-based nanocrystalline soft magnetic powder core according to the present invention, the preparation method of the four-layer coated iron-based nanocrystalline soft magnetic powder core according to this embodiment comprises the following steps:

[0042] S1. Pretreatment: The alloy composition is Fe 73.5 Si 13.5The iron-based nanocrystals of B9Nb3Cu1 were crushed to a median diameter D by ball milling. 50 70-80μm, that is, nanocrystalline magnetic powder;

[0043] S2, one layer of coating: dissolve 1g of phosphoric acid in acetone to form a phosphate acetone solution, add 200g of nanocrystalline magnetic powder into the phosphate acetone solution; the volume of the acetone solution needs to completely cover the surface of the magnetic powder, slowly stir at a stirring speed of 30rmp until the acetone is completely volatilized, at this time, a thin phosphate passivation layer is formed on the surface of the magnetic powder;

[0044] S3, two-layer coating: 8.7g PVP was dissolved in a flask containing 200ml of anhydrous ethanol, and stirred at 40rpm until the solution was uniform and transparent; the passivated magnetic powder was added to the flask, stirred at room temperature for 1h, and the supernatant in the flask was poured out; then NH3·H2O was dripped into the mixed solution of 50% ethanol solution to make the pH of the mixed solution of NH3·H2O and ethanol 10.8, and then the mixed solution was poured into the flask and stirred for 0.5h; 30ml of TEOS was added to anhydrous ethanol and slowly dripped into the flask, and stirred at room temperature for 2h; finally, the magnetic powder was washed with ethanol for more than 2 times, and dried at 100°C to obtain a composite soft magnetic powder coated with SiO2;

[0045] S4, three-layer coating: dissolve 2g of zinc stearate in acetone, add the magnetic powder obtained in step S3 to the zinc stearate / acetone solution, the acetone content must completely cover the surface of the magnetic powder, slowly stir at a speed of 30rpm until the acetone is completely volatilized, so that the zinc stearate is evenly coated on the surface of the nanocrystalline magnetic powder to form a third insulating coating layer;

[0046] S5, four-layer coating: fully dissolve 1g of silicone resin in acetone, add the magnetic powder obtained in step S4 to the acetone solution of silicone resin, the silicone resin acetone solution must completely cover the surface of the magnetic powder, slowly stir at a speed of 30rpm until the acetone is completely volatilized, and the fourth layer coating of the nanocrystalline magnetic powder is completed;

[0047] S6. The magnetic powder obtained in step S5 is pressed in a mold to form an amorphous composite soft magnetic powder core at a pressing pressure of 1800MPa; then, the obtained amorphous composite magnetic powder core is subjected to an appropriate heat treatment process: the sample powder core is placed in a tubular furnace, the air in the furnace is first evacuated to exhaust, and then nitrogen is introduced to place the sample in a nitrogen atmosphere for heat treatment, first the temperature is raised to 510°C and kept for 15 minutes at a heating rate of 20°C / min, and then the temperature is raised to a final temperature of 560°C at a heating rate of 3°C / min. When the final temperature is reached, the heating is stopped immediately, the furnace is opened, and the nitrogen flow rate is increased to cool to room temperature, so as to obtain the iron-based amorphous nanocrystalline soft magnetic composite powder core.

[0048] Example 2

[0049] The difference between this embodiment and embodiment 1 is that: in step S2, the mass ratio of phosphoric acid to nanocrystalline magnetic powder is 1:1000, and the stirring speed is 20rpm; in step S3, the stirring speed of PVP dissolved in ethanol is 30rpm, the mass ratio of passivated nanocrystalline magnetic powder to PVP is 1:30, the pH of the ethanol solution of NH3·H2O is 10.5, and the concentration of passivated nanocrystalline magnetic powder dissolved in TEOS is 0.1g / ml; in step S4, the mass ratio of zinc stearate to magnetic powder is 1:50, and the stirring speed is 20rmp; step S5 In S5, the mass ratio of the silicone resin to the magnetic powder obtained in S4 is 1:200, and the stirring speed is 50rmp; in step S6, the pressing pressure is 2100MPa, the amorphous composite soft magnetic powder core is placed in a tubular furnace, the air in the furnace is exhausted, and then nitrogen is introduced, the temperature is first raised to 480°C, and kept warm for 60 minutes, the heating rate is 10°C / min, and then the temperature is raised to 540°C, and the heating rate is 5°C / min; when 540°C is reached, the heating is stopped, the furnace of the tubular furnace is opened and the nitrogen flow rate is increased, and the four-layer coated iron-based nanocrystalline soft magnetic powder core is obtained.

[0050] Example 3

[0051] The difference between this embodiment and embodiment 1 is that: in step S2, the mass ratio of phosphoric acid to nanocrystalline magnetic powder is 1:800, and the stirring speed is 25 rpm; in step S3, the stirring speed of PVP dissolved in ethanol is 30 rpm, the mass ratio of passivated nanocrystalline magnetic powder to PVP is 1:20, the pH of the ethanol solution of NH3·H2O is 10, and the concentration of passivated nanocrystalline magnetic powder dissolved in TEOS is 0.05 g / ml; in step S4, the mass ratio of zinc stearate to magnetic powder is 1:200, and the stirring speed is 50 rpm; step S5 In S5, the mass ratio of the silicone resin to the magnetic powder obtained in S4 is 1:50, and the stirring speed is 30rmp; in step S6, the pressing pressure is 2400MPa, the amorphous composite soft magnetic powder core is placed in a tubular furnace, the air in the furnace is exhausted, and then nitrogen is introduced, the temperature is first raised to 500°C, kept warm for 15 minutes, the heating rate is 20°C / min, and then the temperature is raised to 555°C, and the heating rate is 1°C / min; when it reaches 555°C, the heating is stopped, the furnace of the tubular furnace is opened and the nitrogen flow rate is increased, so as to obtain the four-layer coated iron-based nanocrystalline soft magnetic powder core.

[0052] Example 4

[0053] The difference between this embodiment and embodiment 1 is that: in step S2, the mass ratio of phosphoric acid to nanocrystalline magnetic powder is 1:400, and the stirring speed is 15 rpm; in step S3, the stirring speed of PVP dissolved in ethanol is 125 rpm, the mass ratio of passivated nanocrystalline magnetic powder to PVP is 1:26, the pH of the ethanol solution of NH3·H2O is 11, and the concentration of passivated nanocrystalline magnetic powder dissolved in TEOS is 0.12 g / ml; in step S4, the mass ratio of zinc stearate to magnetic powder is 1:100, and the stirring speed is 20 rpm; step S5 In step S5, the mass ratio of the silicone resin to the magnetic powder obtained in S4 is 1:10, and the stirring speed is 20rmp; in step S6, the pressing pressure is 2000MPa, the amorphous composite soft magnetic powder core is placed in a tubular furnace, the air in the furnace is exhausted, and then nitrogen is introduced, the temperature is first raised to 490°C, kept warm for 30 minutes, the heating rate is 20°C / min, and then the temperature is raised to 545°C, the heating rate is 2°C / min; when it reaches 545°C, the heating is stopped, the furnace of the tubular furnace is opened and the nitrogen flow rate is increased, and the four-layer coated iron-based nanocrystalline soft magnetic powder core is obtained.

[0054] Comparative Example 1

[0055] The difference between this comparative example and Example 1 is that: in step S2, the mass ratio of phosphoric acid to nanocrystalline magnetic powder is 1:40, and the stirring speed is 100 rpm; in step S3, the stirring speed of PVP dissolved in ethanol is 120 rpm, the mass ratio of passivated nanocrystalline magnetic powder to PVP is 1:10, the pH of the ethanol solution of NH3·H2O is 11.5, and the concentration of passivated nanocrystalline magnetic powder dissolved in TEOS is 0.2 g / ml; in step S4, the mass ratio of zinc stearate to magnetic powder is 1:40, and the stirring speed is 80 rpm; step S5 In S5, the mass ratio of the silicone resin to the magnetic powder obtained in S4 is 1:40, and the stirring speed is 80rmp; in step S6, the pressing pressure is 1750MPa, the amorphous composite soft magnetic powder core is placed in a tubular furnace, the air in the furnace is exhausted, and then nitrogen is introduced, the temperature is first raised to 500°C, kept warm for 30 minutes, the heating rate is 10°C / min, and then the temperature is raised to 560°C, the heating rate is 10°C / min; when it reaches 560°C, the heating is stopped, the furnace of the tubular furnace is opened and the nitrogen flow rate is increased, so as to obtain the four-layer coated iron-based nanocrystalline soft magnetic powder core.

[0056] Comparative Example 2

[0057] The difference between this comparative example and Example 1 is that: in step S2, the mass ratio of phosphoric acid to nanocrystalline magnetic powder is 1:150, and the stirring speed is 100 rpm; in step S3, the stirring speed of PVP dissolved in ethanol is 120 rpm, the mass ratio of passivated nanocrystalline magnetic powder to PVP is 1:35, the pH of the ethanol solution of NH3·H2O is 9.5, and the concentration of passivated nanocrystalline magnetic powder dissolved in TEOS is 0.04 g / ml; in step S4, the mass ratio of zinc stearate to magnetic powder is 1:250, and the stirring speed is 80 rpm; step S5 In step S5, the mass ratio of the silicone resin to the magnetic powder obtained in S4 is 1:250, and the stirring speed is 80rmp; in step S6, the pressing pressure is 2450MPa, the amorphous composite soft magnetic powder core is placed in a tubular furnace, the air in the furnace is exhausted, and then nitrogen is introduced, the temperature is first raised to 510°C, kept warm for 30 minutes, the heating rate is 10°C / min, and then the temperature is raised to 540°C, the heating rate is 10°C / min; when it reaches 540°C, the heating is stopped, the furnace of the tubular furnace is opened and the nitrogen flow rate is increased, and the four-layer coated iron-based nanocrystalline soft magnetic powder core is obtained.

[0058] Comparative Example 3

[0059] The difference between this comparative example and Example 1 is that: step S3 is not included, and in step S2, the mass ratio of phosphoric acid to nanocrystalline magnetic powder is 1:200, and the stirring speed is 100rpm; in step S5, the mass ratio of silicone resin to the magnetic powder obtained in S2 is 1:100, and the stirring speed is 60rmp; in step S6, the pressing pressure is 2000MPa, the amorphous composite soft magnetic powder core is placed in a tubular furnace, the air in the furnace is discharged, and then nitrogen is introduced, the temperature is first raised to 500°C, kept warm for 30min, the heating rate is 10°C / min, and then the temperature is raised to 550°C, the heating rate is 10°C / min; when reaching 550°C, the heating is stopped, the furnace of the tubular furnace is opened and the nitrogen flow rate is increased, and the iron-based nanocrystalline soft magnetic powder core is obtained.

[0060] Effect example

[0061] A scanning electron microscope was used to observe the microstructure of the iron-based nanocrystalline soft magnetic powder cores described in Examples 1-4 and Comparative Examples 1-3 and to measure the thickness of the coating layer. A BH analyzer (IWATSU, SY-8219) was used to measure the magnetic permeability and magnetic loss. The test conditions were: Bm=0.1T, f=50kHz. The test results are shown in Table 1 below.

[0062] Table 1

[0063]

[0064]

[0065] It can be seen from Table 1 that the coating layers of the four-layer coated iron-based nanocrystalline soft magnetic powder cores in Examples 1-4 are all less than 40 nm, and under the test conditions of Bm=0.1T and 50kHz, the magnetic permeability is all greater than 80, and the magnetic loss is all less than 150kW / m 3 , having the advantages of high magnetic permeability and low magnetic loss; while in Comparative Examples 1-3, since the stirring speed or the mass ratio of each component in the process of preparing the coating layer on the surface of the nanocrystalline magnetic powder exceeds the scope of the present invention, the coating layers of the four-layer coated iron-based nanocrystalline soft magnetic powder core are all >1μm, and under the test conditions of Bm=0.1T and 50kHz, the magnetic permeability is all <70, and the magnetic loss is all >170kW / m 3 , and since only three layers of coating were applied to the iron-based nanocrystals in comparative example 3, the final magnetic permeability was only 62, the magnetic loss was as high as 200.5, and the coating layer thickness was greater than that of embodiments 1-4; it can be seen that the four-layer coated iron-based nanocrystalline soft magnetic powder core of the present invention can achieve an ultra-thin coating layer within 40nm through the adjustment of process parameters during the four-layer coating process and the mutual diffusion and mutual migration of each coating layer in the preparation process.

[0066] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing a four-layer coated iron-based nanocrystalline soft magnetic powder core, characterized in that: The following steps are involved: S1. Pretreatment: crushing the iron-based nanocrystals into flaky powder to obtain nanocrystalline magnetic powder; S2. One-layer coating: dissolving a strong acid or a medium-strong acid in ethanol or acetone to form a mixed solution, and adding the nanocrystalline magnetic powder to stir, and after the ethanol or acetone is completely volatilized, a passivation layer is formed on the surface of the nanocrystalline magnetic powder to obtain the passivated nanocrystalline magnetic powder; S3, second layer coating: polyvinyl pyrrolidone is dissolved in anhydrous ethanol and stirred until the solution is uniform and transparent, the passivated nanocrystalline magnetic powder is added, stirring is continued for 0.5-1h, the supernatant is poured out, and then NH3·H2O ethanol solution is dripped into it, stirring is continued for 10-30min, and then a mixed solution of tetraethyl silicate and anhydrous ethanol is dripped and stirred for 1-2h, and finally the passivated nanocrystalline magnetic powder is washed with anhydrous ethanol and dried at 80-100°C, thus completing the second layer coating of the nanocrystalline magnetic powder; S4, three-layer coating: adding the magnetic powder obtained in step S3 to an ethanol or acetone solution of stearate, stirring until the ethanol or acetone is completely volatilized, so that the stearate is evenly coated on the surface of the magnetic powder obtained in step S3, that is, the third layer coating of the nanocrystalline magnetic powder is completed; S5, four-layer coating: adding the magnetic powder obtained in step S4 to an ethanol or acetone solution of an organic silicone resin, and stirring until the ethanol or acetone is completely volatilized, thus completing the fourth layer coating of the nanocrystalline magnetic powder; S6, pressing the magnetic powder obtained in step S5 to obtain an amorphous composite soft magnetic powder core, and then heat-treating the amorphous composite magnetic powder core in a nitrogen atmosphere to obtain the four-layer coated iron-based amorphous nanocrystalline soft magnetic composite powder core; The four-layer coated iron-based nanocrystalline soft magnetic powder core is composed of iron-based nanocrystals and coating layers, wherein the coating layers are respectively a passivation layer, a SiO2 layer, a stearate layer and a silicone resin layer from the inside to the outside, and the thickness of the coating layer is less than 40nm; In step S6, the heat treatment process is specifically as follows: placing the amorphous composite soft magnetic powder core in a tubular furnace, heating it to 480-510°C in a nitrogen atmosphere, keeping it warm for 15-60 minutes, then continuing to heat it to 540-560°C and stopping heating, thereby obtaining the four-layer coated iron-based nanocrystalline soft magnetic powder core.

2. The method for preparing the four-layer coated iron-based nanocrystalline soft magnetic powder core according to claim 1, characterized in that: In step S1, the iron-based nanocrystals are Fe 73.5 Si 13.5 B9Cu1Nb3.

3. The method for preparing the four-layer coated iron-based nanocrystalline soft magnetic powder core according to claim 1, characterized in that: In the step S1, the iron-based nanocrystals are crushed by ball milling to a median diameter D50 of 70-80 μm.

4. The method for preparing the four-layer coated iron-based nanocrystalline soft magnetic powder core according to claim 1, characterized in that: In the step S3, the mass ratio of the passivated nanocrystalline magnetic powder to polyvinyl pyrrolidone is 1:20-30.

5. The method for preparing the four-layer coated iron-based nanocrystalline soft magnetic powder core according to claim 1, characterized in that: In the step S3, the mass ratio of the ethanol solution of NH3·H2O to the passivated nanocrystalline magnetic powder is 2:

1.

6. The method for preparing the four-layer coated iron-based nanocrystalline soft magnetic powder core according to claim 1, characterized in that: In the step S3, the stearate is zinc stearate.

7. The method for preparing the four-layer coated iron-based nanocrystalline soft magnetic powder core according to claim 1, characterized in that: In the step S4, the mass ratio of the stearate to the magnetic powder obtained in the step S3 is 1:50-200.

8. The method for preparing the four-layer coated iron-based nanocrystalline soft magnetic powder core according to claim 1, characterized in that: In the step S5, the mass ratio of the silicone resin to the magnetic powder obtained in the step S4 is 1:50-200.